Examining interhemispheric processing and task demand in lexical decision-making: insights from lateralized visual field paradigm - Kim, Sangyub; Nam, Kichun (Frontiers in Psychology, 2023)
This study aimed to investigate the influence of task demand on the uni-/bi-hemispheric processing of lexical decision-making. Two types of nonwords were used in parafoveal and foveal lexical decision tasks (LDTs) to manipulate task demand. In Experiment 1, a visual half-field paradigm was utilized to evaluate the unihemispheric strategy in lexical decision, which revealed a significant response bias toward ‘word’ at the RVF/LH in the pseudoword LDT in contrast with the nonword LDT, indicating the strategic use of orthographical legality in LH for word-pseudoword lexical decision. In Experiment 2, the study evaluated whether foveal lexical decision follows the orthographical legality strategy of LH in pseudoword LDT relative to the nonword LDT. The results showed a response bias toward ‘word’ in the foveal pseudoword LDT in contrast with the foveal nonword LDT, suggesting the recruitment of LH in foveal pseudoword LDT. These findings support the left-dominant bihemispheric processing in foveal lexical decision and contribute to our understanding of the mechanisms underlying lexical decision-making.